Experiential Teaching Paradigms: Adapting the Medical Education Literature to Academic Pathology Practice - Candice C. Black DO (Elsevier, 2019)
The medical education literature has presented many experiential teaching paradigms to help faculty teach more effectively in busy clinical settings. Three prominent teaching models are The Aunt Minnie model, the SNAPPS model, and the One-Minute Preceptor. Teaching paradigms can help faculty to develop into effective teachers. Each of these models can be adapted to a busy academic pathology practice. The Aunt Minnie model is effective in cases with high pattern recognition, such as repetitive trays of biopsies. The SNAPPS model is learner directed and is easily adapted for an advanced learner with complex cases requiring ancillary testing. The One-Minute Preceptor method is effective for teachers with groups of learners, such as multiheaded scope sessions.